Lennart Nilsson (1922-2017) – Pioneer of embryo photography and his work Ett barn blir till. (May 2023) - Scharf, Jann Lennard; Dracopoulos, Christoph; Gembicki, Michael; Rody, Achim; Welp, Amrei; Weichert, Jan
'Making the invisible visible' is a requirement of a coveted prize for scientific photography – the Lennart Nilsson Award – which is named after the pioneer of human embryo photography. There is no way of avoiding his influence if the hitherto invisible is to be made visible, the intangible almost tangible, the unimaginable made imaginable, and mysteries otherwise hidden from the human eye are to be processed in a popular-scientific way and visualized in an artistic way by means of scientific-medical imaging techniques. Whilst Lennart Nilsson used state-of-the-art imaging technology within the rapidly evolving field of endoscopy, he also created what is probably the best-selling illustrated book of all times with A Child Is Born contributing to both the further understanding of early prenatal development, as well as achieving worldwide popularity.